Creative thinking with stem-based project-based learning model in elementary mathematics learning - Marini; Surmilasari, Nora; Usman, Herlina; Marini, Arita (Universitas Nusantara PGRI Kediri, 2022)
Entering the era of Industrial Revolution 5.0, changes occurred in all aspects, including education. One of the important competencies in this era is the ability to think creatively. In addition, students are also required to be able to integrate their knowledge with science, technology, engineering, and mathematics (STEM). This research is a quasi-experimental research with a non-equivalent post-test only control group design which aims to determine whether is there an effect of using the Project-Based Learning model with STEM-based approach on the creative thinking skills of elementary school students in class V mathematics. The population in This research is the fifth-grade students of SDN 225 Palembang. As for the research sample for the experimental class, students of class V-A and the control class, students in class V-B. The experimental class was treated with Project-Based Learning based on STEM, while the control class used the Project-Based Learning model only. Data collection techniques using tests and data analysis with t-test. Based on the analysis of research data with a significant value of 0.006 < 0.05, it can be concluded that there is an effect of students' creative thinking skills using the STEM-based Project-Based Learning learning model in Mathematics Learning for fifth-grade elementary school.